Correlation of Postvaccination Fever With Specific Antibody Response to Severe Acute Respiratory Syndrome Coronavirus 2 BNT162b2 Booster and No Significant Influence of Antipyretic Medication. (23rd September 2022) - Tani, Naoki; Ikematsu, Hideyuki; Goto, Takeyuki; Gondo, Kei; Inoue, Takeru; Yanagihara, Yuki; Kurata, Yasuo; Oishi, Ryo; Minami, Junya; Onozawa, Kyoko; Nagano, Sukehisa; Kuwano, Hiroyuki; et al.
Abstract: Background: A severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) mRNA vaccine booster elicits sufficient antibody responses that protect against coronavirus disease 2019, whereas adverse reactions such as fever have been commonly reported. Associations between adverse reactions and antibody responses have not been fully characterized, nor has the influence of antipyretic use. Methods: This is a prospective observational cohort study in Japan, following our prior investigation of BNT162b2 2-dose primary series. Spike-specific immunoglobulin G (IgG) titers were measured for SARS-CoV-2–naive hospital healthcare workers who received a BNT162b2 booster. The severity of solicited adverse reactions, including the highest body temperature, and self-medicated antipyretics were reported daily for 7 days following vaccination through a web-based self-reporting diary. Results: The data of 281 healthcare workers were available. Multivariate analysis extracted fever after the booster dose (β = .305, P < .001) as being significantly correlated with the specific IgG titers. The analysis of 164 participants with data from the primary series showed that fever after the second dose was associated with the emergence of fever after the booster dose (relative risk, 3.97 [95% confidence interval, 2.48–6.35]); however, the IgG titers after the booster dose were not associated with the presence or degree of fever after the second dose. There were no significant differences in the IgG titers by the use, type, or dosage of antipyretic medication. Conclusions: These results suggest an independent correlation between mRNA vaccine–induced specific IgG levels and post–booster vaccination fever, without any significant influence of fever after the primary series. Antipyretic medications for adverse reactions should not interfere with the elevation of specific IgG titers. Abstract : Spike-specific IgG titers after a BNT162b2 booster were measured for healthcare workers. Adverse reactions and self-medicated antipyretics were reported. Post–booster vaccination fever was correlated with the specific IgG titers. Antipyretics used for adverse reactions did not suppress specific IgG induction.